Transmodern an art history of contact, 1920-60 - Kravagna, Christian 1962- (Manchester University Press, 2022)
Transmodern examines the global dimension of modern art by tracing the crossroads of modernisms in Asia, Europe and the Americas. It explores path-breaking transcultural art practices from the 1920s to the 1960s in the framework of decolonial movements and transcultural thinking.
Impressum: "This book was originally published as "Transmoderne: Eine Kunstgeschichte des Kontakts" (Berlin: b_books, 2017)"
Keywords: Geschichte 1920-1970; Interkulturalität; Antirassismus; Ästhetik; Abstrakte Kunst; Antikolonialismus; Harlem renaissance; Kunst; Unabhängigkeitsbewegung; Entkolonialisierung; Indien; USA